Tetra-n-butylammonium bis(1,1-dicyanoethylene-2,2-dithiolato)platinum(II) - Kanganga, Nyasha (International Union of Crystallography, 2008)
In the title compound, (C(16)H(36)N)(2)[Pt(C(4)N(2)S(2))(2)], the Pt(II) center adopts a distorted square-planar geometry due to the 4-membered chelate rings formed by coordination to the S atoms of the 1,1-dicyanoethylene-2,2-dithiolate (i-mnt) ligands [bite angle 74.35 (4)°]. The bond distances in the coordinated i-mnt ligands indicate some delocalization of the π-system.